Smart automatic petrol pump system based on internet of things - Zahra'a M. Baqir; Hassan J. Motlak (International Journal of Electrical and Computer Engineering (IJECE), 2021)
IoT is that a rapid expanding program presently for blend all equipment things like (sensors, gadgets, hardware and so on.) assemble and embed those with programming creating our own gadgets use The petroleum pump is these days running physically. it's an activity that fundamentally a drawnout time and requires more workforce. Additionally, put fuel stations in away zones is extermely costly. So achievement an automatic fuel filling system using web technology to solve these problems. There are dense proposed systems which goal to improve the fueling operation so as to form it less difficulty and more dependabl and more-safe, guarinte that the purchaser gets the same quantity of fuel in interchange for what he/she pays, so assist to end fraud at different fuel stations. these systems take human-software interaction by the web-enabeled procedure, thus keep off all errors made by people. The fundamental objective of this review paper is to survey of recent projects in design protype of smart petro pump based on RFID as payment tool and control on it remotely with high security level and concluded with future potential direction in design of smart petrol pump system.